Edukasi Kebutuhan Bayi Balita Asah, Asih, Asuh di Kecamatan Ciseeng Kabupaten Bogor Tahun 2025 - Annisa Fitri Rahmadini; Berliana Apriliani; Shinta Maulidya; Nada Khofia; Putri Apriliani (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
The pattern of asah, asih, asuh is still a priority problem to be resolved in Indonesia. Prevalence data on infants and toddlers with a lack of basic needs such as malnutrition, lack of interest in coming to the integrated health post, and the absence of monitoring of infant and toddler development in Babakan Village, Ciseeng District, Bogor Regency, there are around 20 infants and toddlers who still do not get the correct asah, asih, asuh pattern. This education aims to increase public understanding, especially mothers who have toddlers, regarding the concept of Asah, Asih, Asuh as a holistic approach in supporting child growth and development. This education uses a lecture method with booklet media. Data collection was carried out by distributing questionnaires, the results of the education obtained a p value of 0.000 (p <p = 0.05) which means that there is an influence on increasing knowledge of basic living needs for infants and toddlers asah, asih, asuh as an intervention to prevent unbalanced nutrition and a lack of basic needs for infants and toddlers. And the t value is 6.205. The conclusion of this study is that educational interventions on Asah, Asih, Asuh can increase mothers' awareness and knowledge in caring for and fulfilling the basic needs of infants and toddlers, which ultimately contributes to more optimal child growth and development. It is hoped that the infant and toddler development monitoring program can be implemented at the integrated health post and mothers can better understand the contents of the KIA book.